Synthesis, Spectral and Thermal Studies of Praseodymium(III) and Samarium(III) Complexes with N,N?,N?-Tri(2,4- dihydroxybenzophenone)triaminotriethylamine - Thakur, B.G. (Asian Journal of Chemistry, 2010)
A new Schiff base ligand N,N¢,N²-tri(2,4-dihydroxybenzophenone)- triaminotriethylamine (H6L) has been synthesized. Its complexation behaviour with praseodymium(III) and samarium(III) have been observed. The complexes has been characterized by elemental analysis, IR spectra molar conductivity measurements and thermal analysis. The praseodymium(III) and samarium(III) cations coordinate with the tridentate Schiff base nitrogen atoms, the bridgehead nitrogen atoms and phenolic hydroxyl oxygen atoms.